PENGARUH ASSET GROWTH, FINANCIAL LEVERAGE, DAN LIQUIDITY TERHADAP RISIKO SISTEMATIS PADA SAHAM LQ 45 YANG TERDAFTAR DI BEI PERIODE 2010-2018 - Regina Caeli; Agrianti Komalasari; Komaruddin Komaruddin (Jurnal Akuntansi dan Keuangan (JAK), 2020)
The purpose of this study was to analyze the influence of asset growth, financial leverage, and liquidity to systematic risk of LQ 45 stock that listed in Indonesia Stock Exchange. This study measure systematic risk of stock by using Single Index Model as dependen variable. Independent variables that used are asset growth, financial leverage with proxy degree of financial leverage, and liquidity with proxy current ratio. Samples selection in this study were purposive sampling, which is obtained 12 companies each year within 2010-2018. And the total samples are 108. Analysis method which is used is the panel data by Eviews 10. The result of this study indicate that asset growth and financial leverage has no signifficant effect on systematic risk of stock, while liquidity has negative effect on systematic risk of stock.